Dynamic simulations of compact city development to counter future population decline. (August 2022) - Kikuchi, Hiroki; Emberger, Guenter; Ishida, Haruo; Fukuda, Atsushi; Kobayakawa, Satoru
Abstract: The study simulated the impact of compact city policies on urban services and urban finances by employing a dynamic and spatial land use/transport model. The Metropolitan Activity Relocation Simulator (MARS) was selected as the dynamic and spatial land use/transport model to analyze dynamic urban aggregation changes over time. However, it was not possible to simulate the compact city policies under population decline using the existing MARS. Thus, to dynamically simulate the compact city policies, the MARS was adapted by adding two additional sub-models focused on urban service levels and urban finances. The urban service levels and urban finances were then analyzed during the aggregation process to simulate the policies for a compact city with a declining population. Subsequently, the urban service levels and urban finances were analyzed during the consolidation by simulating the policies for a compact city with a declining population. The findings showed that the disparities in urban areas and suburban public service levels widened, and the local government costs increased by implementing the policy. It was, therefore, concluded that the development of a compact city might be a relief to this situation under continuing population decline, and the implementation of subsidy and preferential treatment policies are greatly required to move residents to urban areas and encourage the compact city. Highlights: MARS dynamically simulates various policy scenarios for analyzing urban service levels and finances. The analysis of urban service levels and finances clarifies the feasibility of compact cities under population declines. The compact city implementation can decrease public facility densities and increase travel costs in suburban zones. Local governments should implement compact city policies and improve urban management efficiency.